Determination of Mercury and Selenium in Tobacco by Inductively Coupled Plasma Mass Spectrometry after Microwave Digestion - HE, RONG; CHEN, JUN; HUANG, ZHANGJIE; YIN, JIAYUAN; YANG, GUANGYU (Asian Journal of Chemistry, 2010)
A new method for the determination of mercury and selenium in tobacco by inductively coupled plasma mass spectrometry (ICP-MS) using isotope dilution calibration was studied. The samples were digested with aqua regia in a microwave oven. The isotope ratios used for quantification were 201Hg/202Hg and 77Se/82Se. A NaBH4 solution was used as reducing agent. Five certified tobacco samples were analyzed and the obtained concentrations were in good agreement with the certified values. The detection limits in the sample were 0.5 and 2 ng g-1, for mercury and selenium respectively. The method is precise, accurate and rapid.